PENGARUH KOMITMEN PROFESIONAL, KOMITMEN ORGANISASIONAL, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA AKUNTAN PENDIDIK, STUDI KASUS PADA UNIVERSITAS DI YOGYAKARTA - Yuni Wulandari; Sumaryanto Sumaryanto (Universitas Ahmad Dahlan, 2015)
The purpose of this research examines for the influences of professional commitment, organizational commitment, and organization culture to the satisfaction of work. The population of this research are the educationalist accountants (the lecturers who have an accountant professional’s degree) from some of universities in Yogyakarta. This research takes samples by using quizioner. The technique of sample’s taking use purposive sampling for the population that has been chosen with responden’s requirement based on those requirement, there are 45 respondents as the sample from 7 universitas in Yogyakarta. Based on the result of analysis, it could be cocluded that the professional commitment and organizational commitment do not give influence to the work;s satisfaction of educatinalist accountants. Otherwise, the organization culture give influence to the work’s satisfaction of educationalist accountants.